Imaging the placental glycocalyx with transmission electron microscopy. (15th December 2018) - Fabre-Gray, Anna C.M.; Down, Colin J.; Neal, Christopher R.; Foster, Rebecca R.; Satchell, Simon C.; Bills, Victoria L.
Abstract: There is a significant glycocalyx present at the maternal-fetal interface of the human placenta, with increasing evidence to suggest it has an important role in placental function. Glycocalyx is adversely affected by traditional tissue processing and fixation techniques. Using transmission electron microscopy, we present methodologies for reliably imaging and measuring glycocalyx of both the syncytiotrophoblast and fetal capillary endothelium in term healthy placentae. These techniques can be used to study the role of the placental glycocalyx in both health and disease, including pre-eclampsia. Highlights: Glycocalyx is present at the maternal-fetal interface of the human placenta. A new method for the ultrastructural imaging of placental glycocalyx is presented. Visualisation of placental glycocalyx is enhanced by these methods. These techniques can be used to study the role of the placental glycocalyx.